دراسة وتحليل البيئة المبنية لمدينة دمشق القديمة وفق مفهوم البيئة المبنية الصديقة للطفل - عبود حنان (Latakia University Journal -Engineering Sciences Series, 2017)
A child friendly city is a city, or any local system of governance, committed to fulfilling children’s rights. It is a city where the voices, needs, priorities and rights of children are an integral part of public policies, programs and decisions. As a result, it is a city that is fit for all. Today, Damascus city rate poorly in terms of the child friendly status. Due to modern planning and zoning practices, planning for the car and uncontrolled growth, children of Damascus are growing up unhealthy, obese and depressed. This research reviews the studies done on the built environment that is convenient for the child’s physical, mental and social health and safety. For the purpose of this research, 64 children (28 girls and 36 boys) aged between 10-14 years, along with their parents were interviewed and asked to describe their perception and experience of the built environment of the New City of Damascus to meet their needs. Then, the research analyses and evaluates the Traditional Damascus Built Environment in order to consider key planning and designing factors that could be learnt through looking at the way the Traditional Built Environment providing for children’s needs, and using this as the blueprint for designing child friendly neighborhoods of new and damaged neighborhood of Damascus City. المدينة الصديقة للطفل هي كل مدينة او بيئة مبنية تلتزم بإنجاز وتطبيق حقوق الطفل. وعلى ذلك، هي كل مدينة تعتبر أصوات واحتياجات واولويات وحقوق الطفل عاملا" مؤثرا في سياساتها وبرامجها وقراراتها العامة. وهي كنتيجة، المدينة التي تلائم الكل. وبناء" على ذلك تصنف مدينة دمشق في مرتبة متأخرة كمدينه صديقة للطفل. في الواقع، يعاني الأطفال في مدينة دمشق، وبسبب تبني النظريات التخطيطية الحديثة ومبدأ فصل الوظائف وإعطاء الأفضلية لحركة السيارات في التخطيط والنمو العشوائي وغير المنظم. من النمو غير السليم وامراض البدانة والسكري وكذلك الاكتئاب. يتناول هذا البحث الدراسات والبحوث السابقة التي تناولت البيئة المبنية المناسبة لصحة الطفل الجسدية والعقلية والاجتماعية وسلامته. وللوصول الى هدف البحث، تم اجراء استبيان ل 64 طفلا" (28 بنت و36 صبي) تتراوح أعمارهم بين 10-14 سنة، وتضمن الاستبيان أسئلة تتعلق بتصورات وخبرات الأطفال عن البيئة المبنية لمدينة دمشق الحديثة ومدى تلبيتها لاحتياجاتهم وتطلعاتهم. ومن ثم يحلل ويقيم البحث البيئة المبنية لمدينة دمشق التقليدية وذلك من اجل استقراء الأسس العمرانية والمعمارية التي يمكن الاستفادة منها في تحديد مبادئ توجيهية وتطبيقية لتحقيق المدن والاحياء والأماكن الصديقة للطفل في مرحلة إعادة الاعمار لأحياء مدينة دمشق المدمرة نتيجة الحرب القائمة حاليا".